PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN JASA DI INDONESIA (STUDI KASUS PADA PERUSAHAAN JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2005-2007) - Sentot Imam; Wahyono Wahyono (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2012)
Purpose of this research is to find the empirical proof that the board composition, board size, the existence of audit committees, company size and managerial ownership affects some earnings management. With Corporate Governance in the company are expected to affect corporate earnings management actions. This research uses the entire population of IDX services company in the year 2005-2007, using purposive sampling techniques sampling the sample obtained by 25 companies. The results using multiple regression analysis is the composition of the board of commissioners, the overall effect of revenue management. This is evidenced by the significance value of 0.002 <0.05. Board size effect on earnings management. This is evidenced by the significance 0.018 <0.05. Audit committees have no effect on earnings management .. This is evidenced by the significance 0.236> 0.05. Size does not affect the company’s revenue management, as evidenced by the value of significance 0.222 <0.05. Managerial ownership has no effect on earnings management, as evidenced by the significance value of 0.581> 0.05.